POST - EXPOSURE MANAGEMENT AGAINST HEPATITIS B VIRUS AT THE DENTAL OFFICE – A REVIEW - DR.M.P.SANTHOSH KUMAR M.D.S. (International Journal of Pharma and Bio Sciences, 2015)
The objective of this paper is to review the modalities of management employed following an accidental exposure to the fatal blood-borne pathogen -Hepatitis B virus. An online search of literature was carried out using the keywords: “Hepatitis B”,” Occupational Exposure”, “Post -exposure prophylaxis”. The information about the post -exposure management against hepatitis B virus in dental office was reviewed.